2021
DOI: 10.3389/fpsyt.2021.701810
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress and Tobacco Use Among Hospital Workers During COVID-19

Abstract: Background and Aims: This work aims to assess the impact of the COVID-19 pandemic on hospital workers' psychological parameters and attitudes toward substance use, before and during the French COVID-19 lockdown.Methods: An online survey was proposed to the staff of the University Hospital of Nice and Sainte-Marie psychiatric hospital in France from May 18 to June 6, 2020 assessing changes in daily habits, psychological distress and changes in substance use, including smoking.Results: A total of 702 respondents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
3
0
1
Order By: Relevance
“…The data indicated a nuanced shift in substance use, with an increase in tobacco use for nearly one-third of participants, which might reflect stress-related behaviors during COVID-19. In 2020, Vanderbruggen et al [ 49 ] found that overall alcohol consumption and cigarette smoking increased during the lockdown, with reasons including boredom and lack of social contacts In 2021, Mounir I et al [ 50 ] reported that hospital workers who experienced increased sadness and distress during the lockdown were more likely to use tobacco. Giovenco et al [ 51 ] highlighted that changes in tobacco use patterns were driven by individual-level factors such as anxiety and irregular routines, as well as limited access to alternative products like electronic nicotine delivery systems.…”
Section: Discussionmentioning
confidence: 99%
“…The data indicated a nuanced shift in substance use, with an increase in tobacco use for nearly one-third of participants, which might reflect stress-related behaviors during COVID-19. In 2020, Vanderbruggen et al [ 49 ] found that overall alcohol consumption and cigarette smoking increased during the lockdown, with reasons including boredom and lack of social contacts In 2021, Mounir I et al [ 50 ] reported that hospital workers who experienced increased sadness and distress during the lockdown were more likely to use tobacco. Giovenco et al [ 51 ] highlighted that changes in tobacco use patterns were driven by individual-level factors such as anxiety and irregular routines, as well as limited access to alternative products like electronic nicotine delivery systems.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is known that nicotine develops modifications in the nervous system that may affect cognition and aspects of emotional behavior [ 51 , 52 ]. In this sense, it has been observed that people tend to increase their TC in periods of increased stress [ 53 , 54 ]. Thus, in this study, we observed that as the EE category increases, so does the prevalence of TC (see Table 2 ), and teachers with high EE have a higher risk of TC (see Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Điều này cho thấy mối quan hệ giữa độ tuổi và triệu chứng tâm lý lo âu ở NVYT, với những người trẻ hơn có khả năng cao hơn bị lo âu. Có thể có những yếu tố như áp lực công việc, trách nhiệm gia đình hoặc tác động của các sự kiện cuộc sống đóng vai trò trong mối quan hệ này [9]. Cụ thể, nghiên cứu chỉ ra NVYT, những người có sử dụng thuốc lá trong thời gian phong tỏa vì COVID-19 cho biết họ cảm thấy buồn bã, lo âu hơn (OR = 1,23, p <0,001) và mất động lực hơn (OR = 0,86, p <0,05) so với những người không hút thuốc.…”
Section: Bàn Luậnunclassified